Design of 4/6 ITI‐mitigating error correction modulation code for ultra‐high‐density bit‐patterned media recording systems. Issue 18 (3rd July 2020) - Nguyen, C.D.
Abstract : A design of 4/6 intertrack‐interference (ITI)‐mitigating error correction modulation code for bit‐patterned media recording systems is proposed in this Letter. Generally, coding schemes in data storage devices are usually accomplished using a combination of error‐correction coding and modulation coding. However, an interesting approach is that the modulation code itself has the capability of correcting errors. Such a modulation code design will reduce the total size and complexity of the data storage devices. In this Letter, the authors design a new 4/6 modulation code, where the code not only mitigates the effect of ITI but also maintains minimum Hamming distance of 2 to build up a trellis structure providing error correction capability of the proposed code. Simulation results show that the proposed design outperforms prior arts. For instance, the performance of the proposed design is better than that of a conventional 4/6 modulation code about 8 dB at a bit error rate of 10 −7 under 20% read‐head offtrack for the area density of 4 Tb/in 2 .